(untitled) (Web of Teachers: Inderscience Research, 2025)
Research in the field of legal terminology is an important and integral part of the scientific activity of jurisprudence. The field explores issues related to legal terms, concepts, and their applications. Legal terminology also serves to improve the effectiveness of the legal system, promote legal culture and expand legal knowledge among citizens. This article details Research in the field of legal terminology, their importance and prospects for development.